Arms export controls and proliferation. - Levine, Paul; Smith, Ron (Journal of Conflict Resolution, 2000)
Part of a special issue on the economic analysis of conflict and related issues. The writers consider a general framework for examining the arms trade and explore the dynamic decision problem confronted by a country deciding whether to make an irreversible investment in arms production capability under conditions of uncertainty. In reviewing a general framework for investigating the arms trade, they outline the process by which optimization by buyers and sellers within a particular supply regime will result in the determination of prices and quantities. Furthermore, they consider the collective action problems faced by suppliers in establishing an arms export control regime and note the incentives for proliferation by existing buyers.